Utilization of The Ayung Watershed (DAS) as A Sustainable Tourism Attraction In Gianyar Regency - Waridin Waridin; I Putu Astawa; Made Ika Prastyadewi; Ika Suciati; Zulfikar Al-Hafidz (Universitas Negeri Malang, 2023)
This study aims to make a list of rules governing the existence and use of watersheds (DAS) in Ubud, try to internalize externalities of watershed utilization, and examine the role of stakeholders in managing watershed utilization in the tourism sector. The sample was selected through ABGC snowball sampling (Academic, Business, Government, and Community). Two types of data are used. Direct observation and in-depth interviews were used to collect primary data. Secondary data is taken from satellite imagery and MAPID.id. The analytical techniques used in this research include stakeholder analysis, descriptive analysis, and literature review. As a consequence of this study, the Tri Hita Karana idea, which was later ratified in a local regulation, was taken into consideration by the management of the Ayung Watershed in the tourism business. Rafting excursions are the only direct use of the Ayung watershed. In addition, the agropolitan and agro-tourism zones of Payangan Regency use water from the Ayung River. To combat the negative externalities associated with the use of the Ayung watershed for tourism, Tri Hita Karana is used. Stakeholders who have great influence and interest in protecting the Ayung Watershed include agriculture, LMDH Pesanggem, and Perhutani.